Evaluation of Bone Marrow Infiltration in Non-Neuropathic Gaucher Disease Patients with Use of Whole-Body MRI – A Retrospective Data Analysis - Laudemann, K.; Moos, L.; Mengel, K. E.; Lollert, A.; Reinke, J.; Brixius-Huth, M.; Wagner, D.; Düber, C.; Staatz, G. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2015)
Purpose: To evaluate whole-body magnetic resonance imaging (WB-MRI) for the assessment of bone marrow infiltration in patients with confirmed Gaucher disease type 1 under long-term enzyme replacement therapy (ERT).Materials and Methods: This retrospective data analysis included 38 patients in two subgroups. Group A: 10 females, 9 males, 15 – 29 years, mean age 22 years and Group B: 11 females, 8 males, 29 – 77 years, mean age 49 years, all treated with alglucerase or imiglucerase for at least 12.5 years. Whole-body MRI was carried out in all patients using a standard MRI protocol. Two radiologists assessed all MR images retrospectively with the use of three different MRI score systems: The bone marrow burden (BMB) score, the Düsseldorf-Gaucher score (DGS) and the vertebra disc ratio (VDR). As a clinical component, severity score index type 1 (GD-DS3) was determined.Results: In both groups the MR scores showed low to moderate pathologic levels but no statistically significant difference was found between both groups. The median scores in group A/group B were 7.00/9.00 for the BMB score (p = 0.07), 4.00/3.00 for the DGS score (p = 0.062) and 1.54/1.62 for the VDR score (p = 0.267). The GD-DS3 score was statistically significantly different between both groups (1.6/3.9, p = 0.000) and osseous Gaucher disease complications were only found in group B.Conclusion: Bone marrow involvement and typical clinical manifestations are reduced to a minimum, when ERT starts immediately after the confirmed diagnosis of Gaucher disease type 1. The applied MR scores are useful markers to control bone marrow infiltration under enzyme replacement therapy in older patients. Pathologic MR scores in young patients may reflect postponed fat conversion of the juvenile bone marrow. This issue has to be examined in further studies.Key Points:• Whole-body MRI is valuable for the staging of Gaucher disease type 1.• Osseous complications are reduced to a minimum in early treated patients.• MR score systems have to be adjusted in young Gaucher patients.Citation Format:• Laudemann K, Moos L, Mengel KE et al. Evaluation of Bone Marrow Infiltration in Non-Neuropathic Gaucher Disease Patients with Use of Whole-Body MRI – A Retrospective Data Analysis. Fortschr Röntgenstr 2015; 187: 1093 – 1098
Keywords: Gaucher disease; whole-body MRI; MRI score system; MR imaging; bones